STUDENT NEEDS FOR INTERACTIVE MEDIA ABOUT HUMAN DIGESTIVE SYSTEM IN SENIOR HIGH SCHOOL - Yola Agustina; Ristiono Ristiono; Ranti Kumalasari (Universitas Negeri Padang, 2022)
The material for the human digestive system is difficult for students to understand, so it requires media that can clarify the material. Limited instructional media at SMAN 1 Tanjung Mutiara has not supported learning on the material. The solution to this problem is to create interactive instructional media. This study aims to identify the needs of students for interactive learning media that developed by Macromedia Flash about human digestive system in senior high school. This type of research is descriptive quantitative. The way to collect data was done trhough distributing questionnaires to students and interviewing one biology teacher. The result revealed that students had difficulty in understanding biology, about the human digestive system material. Because the teaching material were less attractive, the material was too complicated, too many terms were difficult, and they assumed that this material was abstract. Therefore, we need an interactive learning media that is able to help students to understand the learning material.